Antiviral and metabolic gene expression responses to viral infection in Atlantic salmon (Salmo salar). Issue 2 (February 2015) - Heidari, Zeynab; Tinsley, John; Bickerdike, Ralph; McLoughlin, Marian F.; Zou, Jun; Martin, Samuel A.M.
Abstract Salmonid alphavirus (SAV), the aetiological agent of pancreas disease, is recognized as a serious pathogen of farmed Atlantic salmon. This disease results in loss of weight followed by poor growth of surviving fish, as such it is viewed as a wasting disease. SAV and other chronic disease causing viruses affect the heart and skeletal muscle tissues, at present the mechanisms by which pathology occurs is unknown. The relationship between antiviral activity and other physiological parameters especially in skeletal muscle are currently not examined in depth in fish. An experimental SAV (isotype 3) infection was carried out using a cohabitation approach, from which samples were collected at 0, 4, 8 & 12 week post challenge. Maximum viral load in the muscle tissue was 4 weeks post infection which was reduced at 8 weeks and undetectable by 12 weeks. Histopathology score peaked at 4 weeks post infection in pancreas and heart whereas there was maximum damage in skeletal muscle at 8 weeks. The peak expression of antiviral immune genes coincided with the viral load. Several genes involved in protein degradation were increased following infection including atrogin-1 and cathepsin D, at 4 weeks post challenge suggesting reallocation of amino acid reserves. Taken together, these observations increase our understanding of salmon poor growth during viral infection, and will serve as a basis to develop strategies to manage this viral wasting disease.